2006
DOI: 10.3917/emr.123.0085
|View full text |Cite
|
Sign up to set email alerts
|

Réseau, stratégie et gouvernance

Abstract: Résumé Les mutations de notre société influencent radicalement les pratiques managériales et les modes de décision stratégique des entreprises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This was true regardless of homologous recombination repair gene mutation (HRRm) status, though the benefits of combination therapy were greater in men with HRRm (hazard ratio 0.50, 95%CI 0.34-0.73) than men without HRRm (hazard ratio 0.76, 95%CI 0.60-0.97) (39). These results were further confirmed in the phase 3 TALAPRO-2 study, where mCRPC patients treated with the PARP inhibitor talazoparib plus the androgen receptor antagonists enzalutamide had significantly longer ibPFS then mCRPC patients treated with placebo plus enzalutamide (hazard ratio 0.63, 95%CI 0.51-0.78) (40). Again, ibPFS improvement was seen regardless of HRRm status, though again, ibPFS benefits were greater in men with HRRm (HR 0.46, 95%CI 0.30-0.70) than men without HRRm (HR 0.70, 95%CI 0.54-0.89).…”
Section: Discussionmentioning
confidence: 70%
“…This was true regardless of homologous recombination repair gene mutation (HRRm) status, though the benefits of combination therapy were greater in men with HRRm (hazard ratio 0.50, 95%CI 0.34-0.73) than men without HRRm (hazard ratio 0.76, 95%CI 0.60-0.97) (39). These results were further confirmed in the phase 3 TALAPRO-2 study, where mCRPC patients treated with the PARP inhibitor talazoparib plus the androgen receptor antagonists enzalutamide had significantly longer ibPFS then mCRPC patients treated with placebo plus enzalutamide (hazard ratio 0.63, 95%CI 0.51-0.78) (40). Again, ibPFS improvement was seen regardless of HRRm status, though again, ibPFS benefits were greater in men with HRRm (HR 0.46, 95%CI 0.30-0.70) than men without HRRm (HR 0.70, 95%CI 0.54-0.89).…”
Section: Discussionmentioning
confidence: 70%
“…Both TALAPRO-2 (Talazoparib and Enzalutamide) and PROpel (Olaparib and AAP) were conducted in a population of unknown HRR status and showed a benefit for rPFS in the entire population. Moreover, these benefits were observed in both the HRR-mutated and the non-HRR mutated patients (7,8). These results clearly suggested that the combination of PARPi and ARSI could have a synergistic effect, creating a situation similar to that seen in BRCAmutated patients (often referred to as "BRCA-ness").…”
Section: Introductionmentioning
confidence: 80%
“…The phase III trials investigating PARPi in combination with ARSI for mCRPC have not yet been able to confirm or refute this synergistic effect. In MAGNITUDE (6), patients were preselected based on HRRmutation status, while TALAPRO-2 (7) and PROpel ( 8) included an all-comer population and HRR-mutation status was determined after inclusion. These studies cannot be directly compared as they represent different study designs, gene testing strategies and previous exposure to an ARSI.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Randomization was stratified by HRR gene alteration status and previous treatment with life-prolonging therapy in the castration-sensitive setting. The primary endpoint was radiographic PFS, evaluated in the intention-to-treat population, and at the planned primary analysis, median radiographic PFS was not reached (95% CI, 27.5 months-not reached) for talazoparib plus enzalutamide and 21.9 months (16.6-25.1) for placebo plus enzalutamide HR 0.63 (95% CI, 0.51-0.78; p < 0.0001) (21).…”
Section: Introductionmentioning
confidence: 99%